Dynamic Pool Boiling Heat Transfer Due to Exponentially Increasing Heat Input-A Review. (2016) - Walunj, Avdhoot; Sathyabhama, A.
Abstract: The boiling heat transfer, specifically transient or unsteady heat transfer has found much practical importance in the engineering applications. Since, explosive boiling occurs during enormous power excursion in the liquid cooled reactor, the safety evaluation of a nuclear reactor is of vital importance. This paper reviews the transient boiling heat transfer which is the study of transition mechanism from natural convection or nucleate boiling to film boiling and critical point of heat flux using the various wetting fluid as working medium (Distilled water, ethanol, fluorinert liquid, etc.) caused by exponentially increasing heat input at various periods. The survey is also extended to study the heating element (wire, rod, film) usually made of aluminum or platinum under a subcooled or saturated condition of working fluid at atmospheric or higher system pressure. During the quasi-steady or rapid transient, an aspect of dynamic boiling like the onset of boiling, delay period, temperature overshoot, homogenous nucleation, heterogeneous nucleation, transient CHF, bubble growth, vapor coalescence and vapor collapse has been analyzed. Moreover, a visualization study of differently oriented test piece at a different heating rate and different phase of boiling has been qualitatively discussed.